Utilization of Egg Shell Powder as a Filler in Asphalt AC-WC (Asphalt Concrete-Wearing Course) Mixture on Air Flow and Absorption Characteristics - Hijriah Hijriah; Syifa Fauziah; Priyo Wibisono; Ardiansyah Fauzi (Indonesian Journal of Maritime Technology, 2026)
Asphalt Concrete-Wearing Course (AC-WC) is the surface layer of flexible pavement that directly receives traffic loads and protects the underlying layers from the effects of water and weather. The performance of AC-WC is strongly influenced by stability, Marshall flow, air voids, density, and resistance to water absorption. This study utilizes eggshell powder (ESP) as an alternative filler due to its high calcium carbonate content and its potential to fill voids between aggregate particles. The objectives of this study are to determine the optimum asphalt content, determine the optimum ESP content, and evaluate the effect of ESP variations on Marshall flow characteristics and water absorption of AC-WC mixtures. This research was conducted experimentally in the laboratory using ESP variations of 2%, 6%, and 10%. The tests included material characterization, aggregate gradation design, Marshall testing, determination of optimum asphalt content, and water absorption testing. The results show that the optimum asphalt content was 5.24%. The mixture with 6% ESP produced the most balanced performance, with a stability value of 2373.09 kg, Marshall flow of 3.53 mm, VIM of 4.51%, VMA of 20.20%, VFA of 77.67%, density of 2.36 g/cm³, MQ of 673.75 kg/mm, and the lowest water absorption of 0.495%. In terms of flow behavior, the 6% ESP mixture remained within the required specification range, indicating adequate flexibility without excessive deformation. In terms of water absorption, the 6% ESP mixture showed the best resistance to water ingress compared with the 2% and 10% ESP mixtures. The 2% ESP content was insufficient to produce a void structure that met the specifications, while the 10% ESP content tended to increase mixture stiffness and water absorption. Therefore, the use of 6% ESP has the potential to serve as an environmentally friendly alternative filler in AC-WC mixtures, particularly in improving the balance between Marshall flow characteristics and water absorption resistance.